Effect of particle size and annealing on spin and phonon behavior in TbMnO3 - Das, Raja; Jaiswal, Adhish; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Applied Physics, 2011)
Interest has grown to study TbMnO3 as it was recently reported to show a gigantic magnetoelectric effect. Here, we report the synthesis and detailed magnetic and Raman spectroscopy study on TbMnO3 particles of size similar to 25 nm and 2-3 mu m, respectively. The incommensurate-commensurate (lock-in) transition, usually observed at 27 K for bulk phase of TbMnO3 was not observed in susceptibility versus T curve but was seen at 30 K in the coercivity versus T curve in similar to 25 nm particles. This transition, which is due to the spin modulation length scale, gets weakened in nanosize due to the increased intrinsic lattice strain observed in 2-3 mu m particles, due to the effect of increased particle size. The increased value of magnetization in the 2-3 mu m sample was attributed to double exchange interactions between Mn+3 and Mn+4 spins. The role of annealing related effects on the fate of the Neel temperature for TbMnO3 was investigated. Raman spectroscopy indicated a decrease in the lattice distortion for similar to 25 nm particles. (c) 2011 American Institute of Physics. [doi:10.1063/1.3563571]